2014 11th Annual Conference on Wireless on-Demand Network Systems and Services (WONS) 2014
DOI: 10.1109/wons.2014.6814726
|View full text |Cite
|
Sign up to set email alerts
|

Requirement analysis for building practical accident warning systems based on Vehicular Ad-Hoc Networks

Abstract: Abstract-An Accident Warning System (AWS) is a safety application that provides collision avoidance notifications for next generation vehicles whilst Vehicular Ad-hoc Networks (VANETs) provide the communication functionality to exchange these notifications. Despite much previous research, there is little agreement on the requirements for accident warning systems. In order to build a practical warning system, it is important to ascertain the system requirements, information to be exchanged, and protocols needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…It is reported that work in cyber-physical systems pays less attention to early requirements [29,30]. In our approach, through the identification of enterprise capabilities, it is possible to address fully early requirements, and to relate these seamlessly to late requirements.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that work in cyber-physical systems pays less attention to early requirements [29,30]. In our approach, through the identification of enterprise capabilities, it is possible to address fully early requirements, and to relate these seamlessly to late requirements.…”
Section: Discussionmentioning
confidence: 99%
“…These are also reflected in government guidelines such as in the UK document 'Preparing for Emergencies', intended for organisations assisting in civil protection duties (Crichton, Ramsayand, and Kelly 2009). In academia, resilience is described as adaptive capacity to handle the level of environmental complexity and change found on many projects today (Chowdhury, Mackenzie, and Perkins 2014). To be more specific, it is the ability to thrive on change and the ability to adapt to change and develop new approaches (Boin and McConnell 2007;Crichton, Ramsayand, and Kelly 2009).…”
Section: Relationships and Resiliencementioning
confidence: 99%
“…Fig. 3 illustrates how these vectors work and the angle of the two vectors can be calculated as (1). The distance along from the current location B and destination D is calculated based on (2).…”
Section: Dissemination Based On Vehicles' Movementmentioning
confidence: 99%
“…In VANET, real‐time traffic and traveller information services promise unimaginable levels of personal mobility using road status and alarm information. It also poses unique service discovery challenges [1]. For instance, a traffic setting might be saturated with hundreds of vehicles.…”
Section: Service Discovery In Vanetsmentioning
confidence: 99%